2016
DOI: 10.1186/s12864-016-2467-y
|View full text |Cite
|
Sign up to set email alerts
|

Recombination in pe/ppe genes contributes to genetic variation in Mycobacterium tuberculosis lineages

Abstract: BackgroundApproximately 10 % of the Mycobacterium tuberculosis genome is made up of two families of genes that are poorly characterized due to their high GC content and highly repetitive nature. The PE and PPE families are typified by their highly conserved N-terminal domains that incorporate proline-glutamate (PE) and proline-proline-glutamate (PPE) signature motifs. They are hypothesised to be important virulence factors involved with host-pathogen interactions, but their high genetic variability and complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 57 publications
3
88
0
4
Order By: Relevance
“…For MiSeq sequence data, this drop only occurs when the GC content reaches 75% or above. Many regions in the M. tuberculosis genome, especially the pe/ppe genes [24], are high in GC content (median 69%, range 47–87%) and therefore potentially difficult to characterise. The coverage across the 36 drug-resistance candidate genes was high for MiSeq (mean ~90-fold) and exceeded the tenfold cutoff, except in the thyA gene in the three POR1 replicates (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For MiSeq sequence data, this drop only occurs when the GC content reaches 75% or above. Many regions in the M. tuberculosis genome, especially the pe/ppe genes [24], are high in GC content (median 69%, range 47–87%) and therefore potentially difficult to characterise. The coverage across the 36 drug-resistance candidate genes was high for MiSeq (mean ~90-fold) and exceeded the tenfold cutoff, except in the thyA gene in the three POR1 replicates (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is critical in XDR-TB and resistance beyond XDR-TB where use of drugs like PAS may make the difference in providing a life-saving effective regimen of at least five drugs [29]. Large deletions and other structural variants may be detected by applying a combination of complementary approaches (pair-end, split-read and depth of coverage) followed by a validation process involving de novo assembly of bordering reads and re-alignment to the reference genome [10, 16, 24]. However, high genome-wide sequence coverage is necessary to perform such analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, PPE proteins were thought to be involved in antigenic variation and immune evasion (54, 55). While our study identified three novel proteins involved in heme utilization by M. tuberculosis , their molecular functions and how these proteins interact with each other are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…M. tuberculosis exhibits very low sequence diversity compared to other bacteria, minimal evidence of horizontal gene transfer [5355], and recombination limited to known highly variable gene families [28]. This lack of genetic diversity is pronounced in geographically restricted M. tuberculosis populations, such that locally endemic clone groups have posed a unique challenge to laboratory-based identification of TB outbreak clusters in New York City.…”
Section: Discussionmentioning
confidence: 99%
“…SNPs were called using a PHRED-scaled quality threshold of 40 (Samtools v0.1.19 [26]) and annotated using snpEff v4 [27]. We excluded from analysis all variants occuring within PE and PPE genes, a family of highly repetitive, GC-rich M.tuberculosis genes in which recombination has been observed [28]. …”
Section: Methodsmentioning
confidence: 99%